Emission reduction via supply chain coordination. (July 2018) - Zissis, Dimitris; Saharidis, Georgios K.D.; Aktas, Emel; Ioannou, George
Highlights: Environmentally friendly policies are also cost saving. The interrelationship between supply chain coordination and environmental sustainability is investigated. Quantify the environmental impact of a potential coordination on supply chains. COPERT software is used for the calculation of transport emissions and the fuel consumption. Abstract: This paper examines the environmental impact of potential coordination on supply chains. A decentralized two-node supply chain is studied, in which one node is a buyer ordering from a second node, who is a supplier operating under the lot-for-lot policy. The supplier is allowed to use a quantity discount to manipulate the buyer's decision reducing both his individual cost and system's operational costs. This results in decreasing the frequency of deliveries. We demonstrate that environmentally friendly policies could be also cost saving. The crucial factor about the environmental benefits is the total distance travelled rather than the vehicle loads. We establish the magnitude of the environmental benefits using numerical examples under specific operational parameters. Complete and incomplete information cases are investigated, where the buyer and the supplier make their decisions to optimize their own business operations.